2015
DOI: 10.1177/0363546515613068
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Dysplastic Hip Deformities

Abstract: Arthroscopic management of mild to moderate acetabular dysplasia had inferior good/excellent results and higher failure rates when compared with an FAI cohort; therefore, isolated arthroscopic procedures in this population should be cautiously considered. These results were independent of patient sex. Labral repair and capsular plication resulted in better clinical outcomes in this mildly dysplastic cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Hip arthroscopy in patients with mild to moderate acetabular dysplasia, defined by a CE-angle of 19° to 25°, recently demonstrated short-term improvements in post-operative outcome comparable with those with an CE-angle > 25° in a study by Nawabi et al 70 In a similar study, Larsen et al 53 concluded that isolated arthroscopic procedures in patients with dysplasia (average CE-angle 20.8°) leads to improvements in patient outcome, though it was inferior when compared with a FAI cohort. Hence, an improved functional outcome but a high risk of repeated surgery and subsequent THA can be expected.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Hip arthroscopy in patients with mild to moderate acetabular dysplasia, defined by a CE-angle of 19° to 25°, recently demonstrated short-term improvements in post-operative outcome comparable with those with an CE-angle > 25° in a study by Nawabi et al 70 In a similar study, Larsen et al 53 concluded that isolated arthroscopic procedures in patients with dysplasia (average CE-angle 20.8°) leads to improvements in patient outcome, though it was inferior when compared with a FAI cohort. Hence, an improved functional outcome but a high risk of repeated surgery and subsequent THA can be expected.…”
Section: Discussionmentioning
confidence: 90%
“…If these patients are considered for treatment arthroscopically following PAO, it is recommended to inform the patient thoroughly as some studies indicate that hip arthroscopy in this group of patients leads to inferior outcome compared with non-dysplastic FAI patients. 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains controversy in the literature around this topic; while some studies have shown worse postoperative outcomes and high failure rates with hip arthroscopy in patients with hip dysplasia, others have shown equivalent outcomes in patients with mild or borderline hip dysplasia compared with femoroacetabular impingement cohorts. [3][4][5][6][7] Even the lead author has a precautionary paper in this journal about rapid development of osteoarthritis after hip arthroscopy in patients with hip dysplasia. 8 Just because we are doing it, does it mean we should?…”
Section: See Related Article On Page 444mentioning
confidence: 99%
“…Hip arthroscopy has shown positive results in patients with symptomatic femoroacetabular impingement with labral tear. 1 , 2 , 3 There are other structural abnormalities of the hip joint that can make arthroscopic treatment alone less likely to be successful including acetabular dysplasia 4 and femoral version extremes. 5 , 6 , 7 Hip arthroscopy cannot address these morphologic abnormalities, and open surgery is often necessitated to change the underlying cause of the hip pain.…”
mentioning
confidence: 99%